Digital Technology: the Role of Village Volunteers and Local Administration Offices in Controlling Environmental Conditions Associated with Dengue Hemorrhagic Fever Outbreaks: A Case Study from Rong Wua Daeng Sub-District, Sankhamphaeng District, Chiang Mai - มหาสิงห์, สุธีรัตน์; วงค์ชัย, ศิริพร; โปธายะ, วีรพงค์; ศรีกิจการ, เลิศรัก; สุสำเภา, ปฏิพัทธ์; วิศรุตรัตน, สุรสิงห์ (Community and Social Development Journal, 2019)
Dengue hemorrhagic fever is a major public health problem found throughout almost every geographical area in Thailand. Aedes egypti mosquitoes are the most important vectors responsible for transmitting this virus or causing outbreaks of dengue hemorrhagic fever. Thus if Aedes egypti mosquitoes are not present, in a given area, it is impossible for the dengue hemorrhagic fever virus to spread from one person to another. The main objective of this study was to provide community members (i.e. local village health volunteers) and their local administration office a chance to participate in surveillance and prevention efforts aimed at controlling, in a timely manner, the discovery of mosquitoes larvae in rural through the use of digital technology. Results: It was found that the Rong Wua Daeng Sub-district Local Administration and its local volunteers were able to fully monitor the mosquito larvae in this area. There were 160 volunteers participating in surveillance activities(i.e. village health volunteer and other villagers) that were able to report mosquito larva indexes every week from each of the villages in this geographical area. The information from this surveillance system was used as a key input at monthly meeting of the sub-district disease control committee to help them continuously solve problems. As a result of this intervention it was possible to destroy mosquitoes larvae and improve environmental sanitary conditions in this sub-district which, in turn, reduced conditions conducive for the transmission of dengue fever. As such there was a decrease in the number of reported dengue fever cases. During the 2 year period, prior to the introduction of this new digital operational system [i.e. 2016 and 2017], there were 3 reported cases of dengue hemorrhagic fever each year in Rong Wua Daeng sub-district. In 2018 there was only one reported case of dengue fever and that individual contracted the virus while being in another geographical area. There was not any further transmission or outbreaks of the dengue hemorrhagic fever virus in any of communities in Rong Wua Daeng Sub-district. The lesson learned from this intervention is that digital technology can be effectively used in other geographical areas where community-based surveillance is needed to prevent dengue hemorrhagic fever outbreaks, and this requires the active involvement of local government organizations to help solve the dengue hemorrhagic fever problem.